AHP METHOD APPLICATION FOR THE EVALUATION OF INTERNET WEBSITES – COMPUTER SHOPS’ CASE - Chmielarz, Witold (International Journal of Computing, 2014)
The main objective of this paper is an analysis of possibilities of using Saaty’s AHP method in the evaluation of internet websites. The evaluation range is limited to selected websites of the computer shops which are most frequently visited by customers. In the beginning of the article basic assumptions of AHP method are presented. Next, the author shows AHP application in the dimensioning of websites as well as implications resulting from this approach. The last part of this article contains conclusions related to the analysed approach and claims for further research.